Regulation of black-hole accretion by a disk wind during a violent outburst of V404 Cygni - Muñoz-Darias, T; Casares, J; Mata Sánchez, D; Fender, R; Armas Padilla, M; Linares, M; Ponti, G; Charles, P; Mooley, K; Rodriguez, J (Nature Publishing Group, 2016)
Accretion of matter onto black holes is universally associated with strong radiative feedback and powerful outflows. In particular, black-hole transients have outflows whose properties are strongly coupled to those of the accretion flow. This includes X-ray winds of ionized material, expelled from the accretion disk encircling the black hole, and collimated radio jets. Very recently, a distinct optical variability pattern has been reported in the transient stellar-mass black hole V404 Cygni, and interpreted as disrupted mass flow into the inner regions of its large accretion disk. Here we report observations of a sustained outer accretion disk wind in V404 Cyg, which is unlike any seen hitherto. We find that the outflowing wind is neutral, has a large covering factor, expands at one per cent of the speed of light and triggers a nebular phase once accretion drops sharply and the ejecta become optically thin. The large expelled mass (>10(-8) solar masses) indicates that the outburst was prematurely ended when a sizeable fraction of the outer disk was depleted by the wind, detaching the inner regions from the rest of the disk. The luminous, but brief, accretion phases shown by transients with large accretion disks imply that this outflow is probably a fundamental ingredient in regulating mass accretion onto black holes.